Inhibition of mammalian target of rapamycin (mTOR) suppresses UVB-induced keratinocyte proliferation and survival - Carr, Theresa D. (2012)
Ultraviolet (UV) radiation is the major risk factor for developing skin cancer, the most prevalent cancer worldwide. Several studies indicate mammalian target of rapamycin (mTOR) signaling is activated by UVB and may play an important role in skin tumorigenesis. mTOR exists in two functionally and compositionally distinct protein complexes: the rapamycin-sensitive mTOR complex 1 (mTORC1) and the rapamycin-resistant mTOR complex 2 (mTORC2). The purpose of these studies was to investigate the roles of the two mTOR complexes in UVB-mediated proliferation and apoptosis in the skin. We utilized rapamycin, a pharmacological inhibitor of mTORC1, and an inducible mTOR-deficient (K5-CreER(T2);mTOR(fl/fl)) mouse model that allows epidermal-specific disruption of mTOR following topical treatment with 4-hydroxytamoxifen (4OHT). Rapamycin blocked UVB-induced phosphorylation of S6K, the downstream target of mTORC1, and significantly reduced UVB-stimulated epidermal proliferation and cell cycle progression, but had no effect on cell death. In contrast, mTOR deletion, which attenuated UVB-induced phosphorylation of both S6K and the mTORC2 target AKT(Ser473), significantly increased apoptosis both in vivo and in keratinocyte cultures, in addition to reducing hyperproliferation following UVB irradiation. The role of mTORC2 in UVB-induced pro-survival signaling was verified in Rictor(-/-) MEFs, which lack functional mTORC2 and were more sensitive to UVB-induced apoptosis than controls. These studies show that mTORC1 and mTORC2 play unique but complementary roles in controlling proliferation and apoptosis in the skin. Our findings underscore the importance of both mTOR complexes in mediating UVB-induced signaling in keratinocytes and provide new insight into the pathogenesis of skin cancer.